2016
DOI: 10.13005/ojc/320514
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Enaminone-Based Heterocyclic Compounds and Study their Biological Activity

Abstract: We herein reported the utility of 3-(3-(dimethylamino)acryloyl)-2H-chromen-2-one (2), as a versatile precursor for the synthesis of some new azole systems of possible biological activities. The structure of the newly synthesized compounds has been confirmed by IR, 1 H NMR, mass spectral and elemental analysis. Furthermore, some selected compounds were screened in vitro for their anti-microbial activities. The results declared that most of the synthesized compounds have high anti-microbial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It was also concluded that the present C21 steroid can be helpful as a marker for Caralluma genus. As different moieties and functional groups present on synthetic / natural molecules direct their pharmacological activities [30][31][32][33][34][35] , structure activity relationship between such activities and this isolated molecule can be further studied.…”
Section: Fig 2: Luteoline-4-o-neohesperiodosidementioning
confidence: 99%
“…It was also concluded that the present C21 steroid can be helpful as a marker for Caralluma genus. As different moieties and functional groups present on synthetic / natural molecules direct their pharmacological activities [30][31][32][33][34][35] , structure activity relationship between such activities and this isolated molecule can be further studied.…”
Section: Fig 2: Luteoline-4-o-neohesperiodosidementioning
confidence: 99%